Kepastian Hukum, Kemanfaatan dan Keadilan Pemidanaan Kejahatan Asal Usul Perkawinan (Analisis Putusan No. 387/Pid.B/2021/PN.Jmb) - Kurniawan, Ardian; Rafikah, Rafikah; Fitrihabi, Nuraida (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2022)
Abstract: The essence of the purpose of law to realize certainty, expediency, and justice. The rule of law is created not only of juridical value, but also of philosophical and sociological value. This study examines the decision of the Jambi Disterict Court No. 387/Pid.B/2021/PN.Jmb which imposes imprisonment on polygamous perpetrators without the wife's and court's permission. The typology of research is in the form of normative legal research on the object of the study of legal principles with a case approach. This decision implies a conflict of legal certainty with the principle of justice and the usefulness of the law in relation to the position of the convict. Ideally, the punishment of the accused is accompanied by restitution by considering restorative justice, which is not only concerned with punishment and deterrence but also considers the protection of the victim’s family. Keywords: Legal Principles, Court Decisions, Marriage Crime, Illegal Polygamy.